Management of Community Service and Collaboration in Higher Education - Rahayu, Sri; Syaifuddin, Muhammad (Dinasti International Journal of Management Science, 2024)
This research aims to find out how to manage community service and collaboration in higher education. This research method uses literature review or library research namely studies used to collect information and data sourced from reviews, summaries and written thoughts about several library sources in the form of articles, books, slides, information, the internet. The literature used must be relevant, up-to-date and adequate. There are five stages in using the literature review method namely 1) searching for relevant literature, 2) selecting specific sources, 3) identifying article details, 4) creating an outline, 5) compiling literature review. The results of this research show that community service carried out by universities covers many things and is divided into internal or external service. For the external part, lecturers or students go directly into the field and mingle with the community and provide guidance, education and training. Meanwhile, in the university collaboration section, each campus can collaborate with schools, institutions, universities and many more, such as what Telkom University and UIN SUSKA Riau do, and also what UM Metro does with several schools and professional electronics institutions.